Palaeoenvironments and sequence development of the Upper Palaeogene-Lower Neogene Succession in Kirkuk, Bai Hassan and Khabaz oil Fields, Northern Iraq - Yaseen S. Al-Jwaini; Ali D. Gayara (Tikrit Journal of Pure Science, 2023)
Microfacies analysis of the Upper Palaeogene-Lower Neogene succession which include Jaddala, Palani, Sheikh Allas, Shurau, Tarjil, Baba, Bajwan, Ibrahim, Azkand, Anah and Jeribe formations within Kirkuk area led to the recognition of many microfacies. They were grouped into nine facies associations ranging from supratidal to basin setting. These facies associations were deposited within a rimmed shelf with a barrier reef during the Palaeogene and a steepened ramp setting with fringing patch reef during the Neogene. The digenetic imprints on the recognized microfacies are prominent and dominated by cementation, neomorphism, dolomitization, precipitation of authigenic minerals, dissolution (leaching), compaction, mechanical degredation, micritization and geopitalstractures.